Effect of different caloric values on the recovery of marasmic children - Khan, A.; Hayat, N.; Khattak, Muhammad Muzaffar Ali Khan (Karger, 2005)
The effect of diets of different caloric values on the recovery of marasmic children was studied for 3 weeks in Pakistan. Sixty marasmic children of less than 5 years age were grouped in to 4; each group was having 15 children. For each group, two diets, one for early recovery and the other for catch up growth, were prepared from fresh buffalo milk, banana, soybean oil and glucose. The basal (reference) and test diets for early recovery and catch up growth were having constant protein and variable amount of calories. The basal diets and test diets for early recovery and catch up growth were assigned to group 1, 2, 3 and 4 respectively. The early recovery diets were fed for the first 5 days and the catch up growth diets were fed for the remaining period. The recovery of the children was measured in terms of weight gain and weight was taken weekly. The combined average intake/day of the diets was calculated. The average protein intake of groups 1, 2, 3 and 4 were 2.4 ± 0.6, 2.1 ± 0.4, 2.3 ± 1.0 and 2.6 ± 1.0 g/kg body weight/day respectively. The average caloric intake of groups 1, 2, 3 and 4 were 128 ± 32, 129 ± 30, 150 ± 63 and 185 ± 71 Kcal/Kg body weight/day respectively. Children of all the groups gained weight but the groups of test diets gained more weight than the group of basal diet. Group 3 of test diets gained significantly (P< 0.05) more weight than group 1 of basal diet. The data revealed that the diet that provided 2.3 ± 1.0 g protein and 153 ± 63 Kcal/Kg body weight /day was better for the recovery of marasmic children.